2022
DOI: 10.1007/s11104-022-05439-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of salt tolerance in Arabidopsis thaliana on siliceous soils does not confer tolerance to saline calcareous soils

Abstract: Purpose Alkaline salinity constrains crop yield. Previously, we observed local adaptation of Arabidopsis thaliana to saline-siliceous soils (pH ≤ 7) and to non-saline carbonate soils. However, no natural population of A. thaliana was localized on saline-alkaline soils. This suggests that salinity tolerance evolved on saline-siliceous soils may not confer tolerance to alkaline salinity. This hypothesis was explored by addressing physiological and molecular responses to alkaline salinity of A. th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…Reduction of total photosynthetic activity is a common feature of plant stress, and the results confirm that the ability to maintain the photosynthetic capacity is a good indicator of tolerance to either neuSAL or alkSAL in A. thaliana. These observations point to a better performance of demes from pre litoral calcareous soils (V1 PC , LM2 PC ) under alkSAL in terms of growth maintenance and photosynthesis, and agree with the severe reduction in rosette diameter previously reported on coastal demes under alkSAL (Pérez-Martín et al, 2022).…”
Section: Demes From Coastal Siliceous Soils Display Reduced Growth An...supporting
confidence: 91%
See 2 more Smart Citations
“…Reduction of total photosynthetic activity is a common feature of plant stress, and the results confirm that the ability to maintain the photosynthetic capacity is a good indicator of tolerance to either neuSAL or alkSAL in A. thaliana. These observations point to a better performance of demes from pre litoral calcareous soils (V1 PC , LM2 PC ) under alkSAL in terms of growth maintenance and photosynthesis, and agree with the severe reduction in rosette diameter previously reported on coastal demes under alkSAL (Pérez-Martín et al, 2022).…”
Section: Demes From Coastal Siliceous Soils Display Reduced Growth An...supporting
confidence: 91%
“…This suggests that T6 CSadapted to moderate levels of neutral salinity -could be hampered by the alkalinity component of alkSAL. Overall, the observed response of each deme to alkSAL seems driven by other factors than the Na + content in their native soils, as it is the case for neuSAL (Busoms et al, 2018), and reinforces the statement that tolerance to salinity in siliceous soils does not confer tolerance to alkaline salinity (Pérez-Martín et al, 2022).…”
Section: K + and Fe Uptake Efficiency Are Indicators Of Plant Toleran...supporting
confidence: 77%
See 1 more Smart Citation
“…The importance of these genes for tolerance to saline alkaline conditions is further highlighted by the fact that, excepting HKT‐1 , for which absence of allelic variation in the study accessions has been confirmed, the study populations bearing alternative and common allelic variants for each identified locus do not differ in the expression of well‐stablished genes involved in Na and Fe homeostasis such as SOS1 , FRO1 and IRT1 . Recent studies have shown that accessions with tolerance to moderate salinity regulate Na:K ratios under salinity by enhancing HKT1 expression in roots but are unable to increase HKT1 root expression under alkaline salinity (Pérez‐Martín et al., 2022 ). This suggests that mechanisms for a better maintenance of Na:K balance under salinity conditions are likely to differ from those under alkaline salinity and that the latter need to be better understood.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis and rice, plants overexpressing NHXs can retain K + in the cytoplasm under saline conditions, thereby improving salt tolerance [ 10 , 11 ]. Pérez-Martín et al [ 12 ] found that high expression of NHX1 in Arabidopsis leaves under saline and alkaline environment can enhance salt tolerance by promoting Na + partition and osmotic regulation. Plants can improve their tolerance to Na + by collaborating with microorganisms [ 13 ].…”
Section: Introductionmentioning
confidence: 99%